2004
DOI: 10.1021/jm030973k
|View full text |Cite
|
Sign up to set email alerts
|

N,N-Dialkyl-2-phenylindol-3-ylglyoxylamides. A New Class of Potent and Selective Ligands at the Peripheral Benzodiazepine Receptor

Abstract: We report the synthesis and the affinity data at both the peripheral (PBR) and the central benzodiazepine receptors of a series of N,N-dialkyl-2-phenylindol-3-ylglyoxylamide derivatives III, designed as conformationally constrained analogues of 2-phenylindole-3-acetamides II such as FGIN-1-27. Most of the new compounds showed a high specificity and affinity for PBR, with K(i) in the nanomolar to subnanomolar range. The most potent ligands (4-7, 9, 13-27) stimulated steroid biosynthesis in rat C6 glioma cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
199
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(210 citation statements)
references
References 7 publications
8
199
2
Order By: Relevance
“…The shielding and deshielding of the alkyl carbons of the E and Z isomers are consistent with previous 13 C NMR studies, 31−34 which have shown that alkyl carbon atoms syn to amide oxygen are better shielded than the corresponding anti carbons. In particular, the differential shielding of the N-methyl carbon was attributed either to the electric field caused by the carbonyl group 33,34 or to the paramagnetic contribution of the N−C bond of the N-methyl group.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The shielding and deshielding of the alkyl carbons of the E and Z isomers are consistent with previous 13 C NMR studies, 31−34 which have shown that alkyl carbon atoms syn to amide oxygen are better shielded than the corresponding anti carbons. In particular, the differential shielding of the N-methyl carbon was attributed either to the electric field caused by the carbonyl group 33,34 or to the paramagnetic contribution of the N−C bond of the N-methyl group.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…Our calculated NMR chemical shifts for Z 1 , Z 2 , E 1 , and E 2 are, nonetheless, very compatible with experimental findings, and thus, we made no attempts to calculate the weighted NMR chemical shifts. The calculated 13 C chemical shifts for Z 1 ′, Z 2 ′, E 1 ′, and E 2 ′ ( Figure S11, Supporting Information) exhibit a pattern similar to those in Figure 2 and are provided for comparison. Figure 10 also depicts a number of possible interconversion paths among the eight rotamers of 1a.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The ligand with the greatest potency from this class was IND-18 ( Fig. 6) with a K i of 0.37 nM, compared to 9.3 nM for PK 11195 in the same binding assay [20]. Twenty of the most potent ligands from this class were evaluated for their ability to stimulate pregnenolone synthesis in rat C6 glioma cells.…”
Section: Ligandmentioning
confidence: 99%
“…PBR ligands can therefore increase the concentration of neurosteroids in the brain. These neurosteroids, including progesterone, dehydroepiandrosterone and their metabolites, positively modulate γ -aminobutyric acid (GABA) neurotransmission leading to nonsedative anxiolytic effects which are of therapeutic benefit in memory and stress related disorders [20]. Apart from the potential use of PBR ligands in anxiety related disorders, it has been postulated that they could be useful in treating both inflammatory conditions [21,22] and cardiovascular diseases [23].…”
Section: Introductionmentioning
confidence: 99%